Back‐End‐of‐Line Compatible Low‐Temperature Furnace Anneal for Ferroelectric Hafnium Zirconium Oxide Formation. Issue 8 (26th February 2020) - Lehninger, David; Olivo, Ricardo; Ali, Tarek; Lederer, Maximilian; Kämpfe, Thomas; Mart, Clemens; Biedermann, Kati; Kühnel, Kati; Roy, Lisa; Kalkani, Mahsa; Seidel, Konrad
Abstract : The discovery of ferroelectricity in thin doped hafnium oxide films revived the interest in ferroelectric (FE) memory concepts. Zirconium‐doped hafnium oxide (HZO) crystallizes at low temperatures (e.g., 400 °C), which makes this material interesting for the implementation of FE functionalities into the back end of line (BEoL). So far, the FE phase of prior amorphous HZO films is achieved by using a dedicated rapit thermal annealing (RTA) treatment. However, herein, it is shown that this dedicated anneal is not needed. A sole furnace treatment given by the thermal budget present during the interconnect formation is sufficient to functionalize even ultrathin 5 nm HZO films. This result helps to optimize the integration sequence of HZO films (e.g., involving a minimum number of BEoL process steps), which saves process time and fabrication costs. Herein, metal–FE–metal capacitors with Hf0.5 Zr0.5 O2 films of different thicknesses (5–20 nm) are fabricated annealed at 400 °C for various durations within different types of ovens (RTA and furnace). Structural and electrical characterization confirms that all furnace‐annealed samples have similar X‐ray diffraction patterns, remanent polarization, endurances, and thickness dependencies as RTA‐annealed ones. With respect to remanent polarization, leakage current, and endurance, the HZO film of 10 nm thickness shows the most promising results for the integration into the BEoL. Abstract : Herein, it is shown for the first time that no dedicated rapid thermal annealing treatment is needed to form the ferroelectric phase in HZO films. A pure furnace treatment within the thermal budget of the interconnect formation is sufficient to crystallize even ultrathin 5 nm films in the desired ferroelectric (orthorhombic) phase.